Robots or Paws in Service? Lessons from an Inclusive Research Journey by a Dog Owner with Disability - Eszter Loványi (Fogyatékosság és Társadalom)
Based on the author’s personal experiences and research findings, this study introduces the principle of “Nothing About Us Without Us!” and emphasizes the importance of inclusive approaches in the training and use of service dogs. The study proposes a multidisciplinary development as a solution to the service dog versus service robot dilemma. By leveraging technology, “technology-empowered service dogs” are positioned to significantly enhance the well-being of individuals with disabilities. The study highlights the participatory nature of this development, demonstrating how novel and truly usable solutions can be achieved through collaboration with service dog owners. A service dog supported by technology can outperform service robots in tasks that were previously considered their forte. In this “high-tech” project, which focuses on special needs education and technological innovation, not only technical and special needs professionals but also service dog trainers and service dog owners play crucial roles.